2021
DOI: 10.1111/myc.13254
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19–associated pulmonary aspergillosis: a prospective single‐center dual case series

Abstract: Background COVID‐19–associated pulmonary aspergillosis (CAPA) has emerged as an invasive fungal disease, often affecting previously immunocompetent, mechanically ventilated, intensive care unit (ICU) patients. Incidence rates of 3.8%–33.3% have been reported depending on the geographic area, with high (47%) mortality. Objectives Here, we describe a single‐centre prospective case series with CAPA cases from both the first (March‐May, n = 5/33) and second (mid‐September through mid‐December, n = 8/33) COVID‐19 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 38 publications
0
63
2
2
Order By: Relevance
“…BDG 1/? [ 22 ] France 19 Culture 7/9 GM 7/9 PCR – A. fumigatus (14), A. calidoustus (1), A. niger (1) Culture 9/10 GM– PCR – GM 1/12 BDG – [ 23 ] Pakistan 5 Not specified A. fumigatus (1), A. flavus (4), A. niger (1) Not specified GM 0/5 BDG 1/5 [ 24 ] USA 4 Not specified A. fumigatus (4) Not specified GM 1/3 BDG – [ 25 ] France 7 Culture not specified/5 GM 3/5 PCR 2/5 A. fumigatus (5) Not specified GM 1/7 BDG 2/7 [ 26 ] Netherlands 8 Culture 7/7 GM 2/6 PCR 4/5 A. fumigatus (7) Culture 1/1 GM 1/1 PCR 1/1 GM 0/1 [ 27 ] Netherlands 11 Culture 5/40 GM 11/37 PCR 11/40 A. fumigatus (3) Culture 3/47 GM not performed PCR 23/30 GM 0/11 [ 28 ] USA …”
Section: Key Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…BDG 1/? [ 22 ] France 19 Culture 7/9 GM 7/9 PCR – A. fumigatus (14), A. calidoustus (1), A. niger (1) Culture 9/10 GM– PCR – GM 1/12 BDG – [ 23 ] Pakistan 5 Not specified A. fumigatus (1), A. flavus (4), A. niger (1) Not specified GM 0/5 BDG 1/5 [ 24 ] USA 4 Not specified A. fumigatus (4) Not specified GM 1/3 BDG – [ 25 ] France 7 Culture not specified/5 GM 3/5 PCR 2/5 A. fumigatus (5) Not specified GM 1/7 BDG 2/7 [ 26 ] Netherlands 8 Culture 7/7 GM 2/6 PCR 4/5 A. fumigatus (7) Culture 1/1 GM 1/1 PCR 1/1 GM 0/1 [ 27 ] Netherlands 11 Culture 5/40 GM 11/37 PCR 11/40 A. fumigatus (3) Culture 3/47 GM not performed PCR 23/30 GM 0/11 [ 28 ] USA …”
Section: Key Questionsmentioning
confidence: 99%
“…The performance of LFD tests has been studied in ICU patients [ 30 ], showing a good overall test performance (sensitivity 0.88–0.94, specificity 0.81, and the area under the ROC curve 0.90–0.94) [ 30 ]. AspLFD (OLM Diagnostics) was used in 8 CAPA cases using one TA and seven BAL samples [ 27 ]. The AspLFD was positive in six patients but did not correspond with GM detection in four.…”
Section: Key Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meijer and others conducted a small-sample cohort study (66 ICU patients with COVID-19) and found that the incidence of CAPA was 19.7% (n = 13/66), and the fatality rate of a single study was 46.2% (6/13); the author's team listed some of the articles that have been published and analysed for the CAPA fatality rate. The pooled CFR for CAPA was 47% (62/132) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 29 studies, (27.59%) were from France [2,13,[21][22][23][24][25][26]], 4 (13.79%) were from the United Kingdom (UK) [27][28][29][30][31][32], 4 (13.79%) were from the Netherlands [33,34], 2 (6.90%) were from Germany [35,36], 2 (6.90%) were from Spain [15,37], 2 (6.90%) were from Switzerland [14,38], 1 (3.45%) was from the USA [39], 1 (3.45%) was from Belgium [40], 1 (3.45%) was from China[6], 1(3.45%) was from Pakistan [41], 1(3.45%) was from Denmark [42], 1 (3.45%) was from Italy [43] and 1(3.45%) from Mexico [44]. Twelve studies dealt with patients who received mechanical ventilation, eight studies were of patients with ARDS, one study was on extracorporeal membrane oxygenation (ECMO), 1 study looked at acute respiratory failure (ARF), and seven studies included other patients with severe COVID-19 (See additional le 1, supplementary 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%